PERSEPSI MASYARAKAT DALAM UPAYA PENGENDALIAN KEBAKARAN HUTAN DI TAMAN NASIONAL GUNUNG CIREMAI Community Role to the Forest Fire Control in Mount Ciremai National Park - Bambang Hero Saharjo; Guntala Wibisana (Jurnal Silvikultur Tropika, 2017)
Forest fires cause losses and negative impact. Forest fire in mountain Ciremai national park caused by human factor. Efforts to control forest fires currently preferred by involving the community. This research is done using primary data and information obtained from filling the questionnaire. Research is taking samples from three villages namely Cibuntu village, Padabeunghar villages, and Kaduela village. Respondents were interviewed 90 respondents. Based on researches known that the area around the national park had high perception of Ciremai national existance. They argue that the mountain Ciremai national parks useful in life and the management of mountain Ciremai national parks better. Based on the scoring of 90 respondents 70 of them have a highperception of the forest fire control in mountain Ciremai national park, it means that most of people have participated in efforts to control forest fire.Key words: Forest fire,community role, forest fire control